Development of the MCDL Day's Instrument as a Personality Measurement Tool compared to the Papikostick Test Tool - Muhammad Syarif Hidayatullah; Hayatun Thaibah; Aisyah Putri Maulidina; Muhammad Zidan Ramadhan (Universitas Ahmad Dahlan, 2022)
In the working world, the personality of a worker or employee is one of the crucial things to know. Personality can be seen from various things, including behavior patterns, to understand better how someone acts in certain situations. This study looks at the MCDL Day's Instrument as a personality measurement tool compared to the Papikostick test. This research method uses a cross-sectional quantitative approach. The research subjects were 235 people aged 17-34 years. The reliability test used a composite score. The validity test used confirmatory factor analysis (CFA) and concurrent criteria. The results showed that the reliability test of the composite score is 0.616 with the results of the CFA loading factor 0.30 with 18 valid items and four dimensions explaining 23% of the variables. For the criteria validity, there is no significant relationship between the MCDL Day's instrument and the dimensions in Papikostick.